A numerical realization of Lunar time ephemeris and its harmonic decomposition - Tian, W. (2025)
Similar to time ephemeris of the Earth, Lunar time ephemeris (LTE) rep resenting the difference between TDB/TCB and lunar time scales, such as, TCL (Lunar Coordinate Time) recommended in Resolution II at the IAU2024 General Assembly, will play essential roles in time-keeping on the Moon. In this talk we will report a numerical realization of LTE which is consis tent with the planetary and lunar ephemeris PETREL19 [1]. For practical use, a harmonic decomposition of LTE is implemented with the method of Kudryavtsev(2004) [2], At last, the lunar time scales (implicitly) adopted by different LLR (Lunar Laser Ranging) analysis groups will be reviewed, and the impact of selecting different lunar time scales on the realization of lunar reference frames will be discussed.